Global patterns in leaf (13)C discrimination and implications for studies of past and future climate - Diefendorf, Aaron F. (National Academy of Sciences, 2010)
Fractionation of carbon isotopes by plants during CO(2) uptake and fixation (Δ(leaf)) varies with environmental conditions, but quantitative patterns of Δ(leaf) across environmental gradients at the global scale are lacking. This impedes interpretation of variability in ancient terrestrial organic matter, which encodes climatic and ecological signals. To address this problem, we converted 3,310 published leaf δ(13)C values into mean Δ(leaf) values for 334 woody plant species at 105 locations (yielding 570 species-site combinations) representing a wide range of environmental conditions. Our analyses reveal a strong positive correlation between Δ(leaf) and mean annual precipitation (MAP; R(2) = 0.55), mirroring global trends in gross primary production and indicating stomatal constraints on leaf gas-exchange, mediated by water supply, are the dominant control of Δ(leaf) at large spatial scales. Independent of MAP, we show a lesser, negative effect of altitude on Δ(leaf) and minor effects of temperature and latitude. After accounting for these factors, mean Δ(leaf) of evergreen gymnosperms is lower (by 1–2.7‰) than for other woody plant functional types (PFT), likely due to greater leaf-level water-use efficiency. Together, environmental and PFT effects contribute to differences in mean Δ(leaf) of up to 6‰ between biomes. Coupling geologic indicators of ancient precipitation and PFT (or biome) with modern Δ(leaf) patterns has potential to yield more robust reconstructions of atmospheric δ(13)C values, leading to better constraints on past greenhouse-gas perturbations. Accordingly, we estimate a 4.6‰ decline in the δ(13)C of atmospheric CO(2) at the onset of the Paleocene-Eocene Thermal Maximum, an abrupt global warming event ∼55.8 Ma.